The influence of coach turnover on student-athletes' affective states and team dynamics: An exploratory study in collegiate sports. Issue 1 (February 2019) - Shipherd, Amber M; Wakefield, Joann C; Stokowski, Sarah; Filho, Edson
Coach turnover is frequent, especially in collegiate sports in the United States. To date, however, there is limited research on how coach turnover might affect student-athletes. Accordingly, we aimed to qualitatively explore how coach turnover might influence student-athletes' psychosocial states and team dynamics in collegiate sports. Eleven athletic teams at a Midwestern Division I National Collegiate Athletic Association institution having undergone coach turnover during the past four years participated in the study. Four coaches and 21 student-athletes representing both individual and team sports, as well as two administrative staff members, participated in semi-structured interviews (coaches and administrators) and focus groups (student-athletes). Inductive data analysis revealed four first level themes: coach style and background, athlete affective states, team dynamics, and program culture. Our analysis suggested that, depending on their gender and coaching style, coaches might have a positive or negative impact on athletes' affective states (e.g. positive and negative affect), team dynamics (e.g. cohesion; athlete leadership), and the program culture. Thus, practitioners might facilitate the positive impact of coaching turnover by assessing whether the new coach is a 'good fit' at the individual (micro), team (meso), and environmental (macro) level of analysis.